KESESUAIAN KURIKULUM KETERAMPILAN VOKASIONAL DENGAN TUGAS PERKEMBANGAN DAN TUNTUTAN KOMPETENSI DUNIA KERJA BAGI ANAK TUNAGRAHITA SEDANG DI SLB C "X" KOTA BANDUNG : Studi Kasus Kelas Anak Tunagrahita Sedang - Julia, Salma (2011)
Kenyataan bahwa anak tunagrahita memiliki kesulitan dalam mendapatkan kesempatan bekerja di masyarakat menjadi latar belakang tesis ini. Penelitian studi kasus ini dilakukan pada kelas tunagrahita sedang tingkat SMALB. Fenomenanya adalah kurikulum SMALB bagi anak tunagrahita sedang, tugas perkembangan dan tuntutan dunia kerja yang tersedia bagi mereka. Dokumen RPP menjadi satu komponen acuan tertulis mengenai isi kurikulum untuk dicocokkan dengan tugas perkembangan hasil dari wawancara kepada orang tua siswa. Hasil akhir dari penelitian ini ternyata bahwa kurikulum keterampilan vokasional yang diberikan kepada tunagrahita sedang di SLB C "X" belum sesuai dengan tugas perkembangan tunagrahita sedang. Kurikulum tersebut belum diperlengkapi dengan pencapaian kompetensi perilaku adaptif yang diperlukan di dunia kerja. Program prevokasional untuk mempersiapkan motorik dan tingkah laku anak tunagrahita pun belum menjadi fokus kurikulum di satuan jenjang di bawah SMALB. The facts have been shown us that the mentally retarded students have very limited chances to get a job. This issue become a background of this research. This is a study case of a moderate mentally retarded senior high class at a special school for students with mental retardation. The phenomena are the curricullum, the developmental tasks and competence demands of the workplace for moderate mentally retarded students. The main informants were a principal, senior high class teachers, parents of moderate mentally retarded students, vocational teachers, elementary school teachers. The secondary informant are woven doormat home industrialists. The reasons of choosing woven doormat home industry as the informants are because weaving doormat is one of vocational skills that is taught to mentally retarded students at the school and woven doormat is one of products that is still needed by people. We can see it everywhere. it means that weaving doormat is one of products that have a good future. So that the mentally retarded people can earn their own life by weaving it. After observing, interviewing them and collecting important documents, all data collected are processed. The lesson plans of academic subjects and vocational subjects become a referrence component of curriculum content. The curriculum content, then, is matched to the developmental task of the moderate mentally retarded students and compentences needed at the workplace. The final result of analising data is that the senior high vocational curriculum for mentally retarded students has not been congruent to the development task of moderate mentally retarded students. That is why moderate mentally retarded students are not ready to do their job at the workplace. The competences that has not been planned for them, especially they have not been prepared for their adaptive behaviour.